Modeling cross-scale relationships between climate, hydrology, and individual animals: generating scenarios for stream salamanders - Girard, Philippe; Levison, Jana; Parrott, Lael; Larocque, Marie; Ouellet, Marie-Audray; Green, David M. (Frontiers in Environmental Science, 2015)
Hybrid modelling provides a unique opportunity to study cross-scale relationships in environmental systems by linking together models of global, regional, landscape, and local-scale processes, yet the approach is rarely applied to address conservation and management questions. Here, we demonstrate how a hybrid modelling approach can be used to assess the effect of cross-scale interactions on the survival of the Allegheny Mountain Dusky Salamander (Desmognathus ochrophaeus) in response to changes in temperature and water availability induced by climate change at the northern limits of its distribution. To do so, we combine regional climate modelling with a landscape-scale integrated surface-groundwater flow model and an individual-based model of stream salamanders. On average, climate scenarios depict a warmer and wetter environment for the 2050 horizon. The increase in average annual temperature and extended hydrological activity time series in the future, combined with a better synchronization with the salamanders’ reproduction period, result in a significant increase in the long-term population viability of the salamanders. This indicates that climate change may not necessarily limit the survivability of small, stream-dwelling animals in headwater basins located in cold and humid regions. This new knowledge suggests that habitat conservation initiatives for amphibians with large latitudinal distributions in Eastern North America should be prioritized at the northern limits of their ranges to facilitate species migration and persistence in the face of climate change. This example demonstrates how hybrid models can serve as powerful tools for informing management and conservation decisions.